Survey of haemosporidian parasites in resident and migrant game birds of Illinois. - Annetti, Kendall L.; Rivera, Nelda A.; Andrews, John E.; Mateus-Pinilla, Nohra E. (Journal of Fish and Wildlife Management, 2017)
Haemosporidian parasites are globally distributed in avian species, and are capable of leading to decreased reproductive success, weakness, and mortality. Bird conservation groups and organizations concerned with the health and immunological status of avian populations are interested in haemosporidian parasites that affect reproduction and population growth. Haemosporidian infection data are not yet always available for some avian species in specific regions. These data provide the starting points for researchers to evaluate geographical and temporal changes in the patterns of infection and prevalence across populations. We examined haemoparasite infections in four game bird species commonly hunted in Illinois. We calculated prevalence, mean intensity, median intensity, and mean abundance of haemosporidians, and evaluated the relation of these infection measures associated with age and sex of the avian hosts. Game species sampled (N = 237) included migrants such as mourning doves Zenaida macroura, wood ducks Aix sponsa, and Canada geese Branta canadensis, as well as resident birds such as wild turkeys Meleagris gallopavo. We identified only Haemoproteus, Plasmodium, and Leucocytozoon species. Haemoproteus was the most prevalent haemosporidian (46/237), followed by Plasmodium (11/237). Furthermore, Haemoproteus was the most persistent haemosporidian, as it was the only parasite genera that we found in all four avian species. We found coinfections in 55% of turkeys, but found no significant correlations between the genera of haemosporidinan coinfections and a host species. Moreover, no significant differences in the proportion of infected individuals (prevalence) and haemosporidian quantities (levels of intensity and abundance) were related to biotic factors such as age and sex of the host. However, parasite aggregation (distribution of parasites among hosts) was affected by age, as adult turkeys and juvenile doves showed the highest aggregation index (Poulin's index of discrepancy) for Haemoproteus spp. This ...